The Critical Discourse Analysis of Some Inclusion Components and the Representation of Social Actors in “Bijan and Manijeh” Story: A Sociological-Semantic Approach - Abbas Ali Ahangar; Mohammad Amir Mashhadi; Zeinab Teimuri Rabor (زبان پژوهی, 2023)
One of the topics that many linguists have considered in recent years is discourse analysis. Different researchers have presented and developed various points of view about critical discourse analysis such as Hodge and Kress (1976), Foucault (1980), Fairclough (1996 and 2002), Penny Cook (2001), Wodak and Meyer (2001), Mouffe (2001), Van Dijk (2004) and Van Leeuwen (1996, 2008) among others. In this regard, Van Leeuwen's (2008) critical discourse analysis model is a socio-semantic model, which rests on interactions, actions, and reactions between individuals. In fact, the present study has exclusively been carried out based on this model in order to understand how social actors are represented and also to see whether the application frequency of various discourse components related to inclusion in the story of "Bijan and Manijeh" from Ferdowsi's Shahnameh is significant or not.    The components of inclusion under discussion having been analyzed in accordance with this model are as follows: 1) Association, the way to represent the social actors in a group and bring them together in an action. 2) Activation, the component that is used when social actors are active and are dynamically represented. 3) Differentiation, which refers to a situation in which social actors are differentiated from other actors because of their identities. 4) Nomination, which is divided into types of sub-components of formal nomination, informal nomination, semi formal nomination, and titulation. In formal nomination, social actors are introduced by referring to their last names and in informal nomination they are represented only by their first names. In semi-formal nomination, social actors are represented by their first and last names and in titulation they are referred to by titles. 5) Specification, which is divided into three sub-components: Individualism, Aggregation, and Collectivization. Individualism is a device to represent social actors by referring to a specific and unique name, collectivization means representing social actors by referring to general classes and groups, and aggregation denotes representing actors by referring to numerical sets (Van Leeuwen, 2008).   The text under study in this research is the story of "Bijan and Manijeh" taken from Ferdowsi's Shahnameh. This poem comprises a total of 1312 verses out of the entire Shahnameh book. This story is made of a series of events that are perfectly connected. In the first verses of the story, the poet speaks about a female storyteller who has narrated the whole story to him, and the poet tells this story to readers again. By considering the importance of the Shahnameh book and using the discourse-oriented components related to inclusion as developed in Van Leeuwen's (2008) model, we can deal with how social actors are represented in the text of this story and then the way it is possible to describe, compare and analyze the application frequency of each component and the relevant sub-components. Correspondingly, the questions of the present study are as follow:How are the types of discourse components of inclusion in Van Leeuwen's (2008) model under investigation represented in the "Bijan and Manijeh" story?What kind of relationship exists between the application frequency of the various inclusion components analyzed following Van Leeuwen's (2008) model in "Bijan and Manijeh" story?According to these questions, the hypotheses of this study are as the following:Different types of discourse components of inclusion under investigation are represented in accordance with the discourse components of Van Leeuwen's (2008) model in "Bijan and Manijeh" story.There is a significant relationship between the application frequency of different inclusion components analyzed following Van Leeuwen's (2008) model in "Bijan and Manijeh" story.